Multiscale molecular profiling of pathological bone resolves sexually dimorphic control of extracellular matrix composition - Aikta Sharma; Alice Goring; Peter B. Johnson; Roger J. H. Emery; Eric Hesse; Alan Boyde; Bjorn R. Olsen; Andrew A. Pitsillides; Richard O. C. Oreffo; Sumeet Mahajan; Claire E. Clarkin (The Company of Biologists, 2021)
Collagen assembly during development is essential for successful matrix mineralisation, which determines bone quality and mechanocompetence. However, the biochemical and structural perturbations that drive pathological skeletal collagen configuration remain unclear. Deletion of vascular endothelial growth factor (VEGF; also known as VEGFA) in bone-forming osteoblasts (OBs) induces sex-specific alterations in extracellular matrix (ECM) conformation and mineralisation coupled to vascular changes, which are augmented in males. Whether this phenotypic dimorphism arises as a result of the divergent control of ECM composition and its subsequent arrangement is unknown and is the focus of this study. Herein, we used murine osteocalcin-specific Vegf knockout (OcnVEGFKO) and performed ex vivo multiscale analysis at the tibiofibular junction of both sexes. Label-free and non-destructive polarisation-resolved second-harmonic generation (p-SHG) microscopy revealed a reduction in collagen fibre number in males following the loss of VEGF, complemented by observable defects in matrix organisation by backscattered electron scanning electron microscopy. This was accompanied by localised divergence in collagen orientation, determined by p-SHG anisotropy measurements, as a result of OcnVEGFKO. Raman spectroscopy confirmed that the effect on collagen was linked to molecular dimorphic VEGF effects on collagen-specific proline and hydroxyproline, and collagen intra-strand stability, in addition to matrix carbonation and mineralisation. Vegf deletion in male and female murine OB cultures in vitro further highlighted divergence in genes regulating local ECM structure, including Adamts2, Spp1, Mmp9 and Lama1. Our results demonstrate the utility of macromolecular imaging and spectroscopic modalities for the detection of collagen arrangement and ECM composition in pathological bone. Linking the sex-specific genetic regulators to matrix signatures could be important for treatment of dimorphic bone disorders that clinically manifest in pathological nano- and macro-level disorganisation. This article has an associated First Person interview with the first author of the paper.